Social Entrepreneurship and Water Disclosure: A Bibliometric Analysis - Santoso, Arif; Sari, Puji Novita; Rahayu, Selvia; Lestari, Sari; Srimaryani, Srimaryani (Journal of Economics Education and Entrepreneurship, 2024)
In a world increasingly concerned with environmental sustainability and corporate responsibility, the relationshiop between water disclosure, social entrepreneursip, and the cultivation of the entrepreneurship ecosystem emerges as a critical nexus. Water is the essensial need for human life and business life. Entrepreneurial concern for these issues also influences access to financing and market. These problems have received much attention from researcher, but there has been no attempt to synthesize the results. This research aim to explores and synthesize the literature related water disclosure and social entrepreneurship in the entrepreurship ecosystem. The analysis was based on Scopus database in the last decade and PRISMA protocol and VOSViewer was used. This study performs co-occurrence and co-authorship analysis. Social entrepreneurship, sustainability, innovation, water disclosure, and strategy are some of the frequently emerging variables. The results of network analysis show that social entrepreneurship and water disclosure are linked by variable stakeholder, economic and social effect, and sustainable development. It highlights that water disclosure and social entrepreneurship is a mandate of the stakeholders and its implication is that the entrepreneurial ecosystem has moved towards sustainable development.